DESKRIPSI DAN PREFERENSI HABITAT UDANG AIR TAWAR MACROBRACHIUM ROSENBERGII (DE MAN, 1879) DARI SUNGAI MARAJA, TOLI-TOLI, SULAWESI TENGAH - Aswandi, Aswandi; Annawaty, Annawaty (Univ. Tadulako, 2019)
Macrobrachium rosenbergii (De Man, 1879) is a freshwater prawn species that have a high economic value because of its relatively large size compared to the other freshwater prawn species. Exploration to find this species in the Maraja River, Toli-Toli, Central Sulawesi was carried out in January 2019. Sample collected using tray net. Two male specimens of M. rosenbergii were found in the river, with maximum size of carapace length reaching 45.94 mm. Macrobrachium rosenbergii has been found in habitats with clay substrate and slow flowing current. This record extended the distribution of M. rosenbergii, whose spread in Sulawesi has been known only in the southern part of the island, such as in Makassar, Bone, Pinrang, Wajo and Luwu. In this paper, the morphological characters and line drawing of some character M. rosenbergii from the Maraja River were provided.